Functional Gonadotroph Adenomas: Case Series and Report of Literature. Issue 6 (December 2016) - Cote, David J.; Smith, Timothy R.; Sandler, Courtney N.; Gupta, Tina; Bale, Tejus A.; Bi, Wenya Linda; Dunn, Ian F.; De Girolami, Umberto; Woodmansee, Whitney W.; Kaiser, Ursula B.; Laws, Edward R.
Abstract : BACKGROUND: Functional gonadotroph adenomas (FGAs) are rare tumors of the pituitary gland that secrete biologically active gonadotropins. OBJECTIVE: To advance clinical understanding of FGAs. METHODS: We performed a retrospective review of adult patients who underwent resection of a pituitary lesion between August 1997 and October 2014 and remain under care at our center. We identified patients who had pathologic and biochemical confirmation of FGAs, as defined by a lack of serum follicle-stimulating hormone/luteinizing hormone suppression in the setting of elevated gonadal steroids, associated clinical symptoms, or both. RESULTS: FGAs were documented in 7 patients (5 men, 2 women) over a 17-year period. Clinical findings at presentation included visual field deficits in 5 patients, headache in 3, sexual dysfunction in 3, and ovarian cysts in both women. Each patient underwent lesion resection (6 via the endonasal transsphenoidal approach and 1 via a craniotomy with transsphenoidal reoperation). Analysis of tumor samples revealed immunopositivity for follicle-stimulating hormone/luteinizing hormone in 5 patients and FSH only in 2 patients. Postoperative follow-up (median, 10 months; range, 4-213 months) indicated remission in 6 of 7 patients. CONCLUSION: An FGA can pose both a diagnostic and a therapeutic challenge. The tumor is often diagnosed as a nonfunctioning macroadenoma after presenting with nonspecific symptoms and is the cause of significant morbidity. An FGA should be considered in the differential diagnosis of patients harboring pituitary adenomas with reproductive dysfunction. Transsphenoidal resection is the initial treatment of choice and can reduce endocrine dysfunction, resolve headaches, improve visual impairment, and provide tissue for detailed analysis. ABBREVIATIONS: FGA, functional gonadotroph adenoma FSH, follicle-stimulating hormone LH, luteinizing hormone TSH, thyroid-stimulating hormone Abstract : Supplemental Digital Content is Available in the Text.